The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2007
DOI: 10.1586/14787210.5.4.581
|View full text |Cite
|
Sign up to set email alerts
|

Beyond the end of exceptionalism: integrating HIV testing into routine medical care and HIV prevention

Abstract: In September 2006, the US CDC issued new guidelines for HIV testing. These guidelines were designed not only to simplify and expand HIV testing but also to integrate testing into routine medical care in the USA. The nationwide implementation of these guidelines is currently facing several political and legal barriers. In this article, we examine the origins of current patient-driven and risk-based HIV testing in the USA and highlight shortcomings of this strategy. We then demonstrate how the changing HIV epide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 43 publications
1
8
0
Order By: Relevance
“…Until then, established testing protocols and implementation of routine HIV RNA testing should be expanded. 9,10,30,31 Our data also demonstrate that increased behavioral risk among MSM is associated with acute HIV infection. If pooled HIV RNA testing is not performed on those with negative HIV rapid tests, over 10-15% of testers in high-risk groups may be missed and sent home unaware of their actual infection status at the height of their infectivity and sexually risky behaviors.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Until then, established testing protocols and implementation of routine HIV RNA testing should be expanded. 9,10,30,31 Our data also demonstrate that increased behavioral risk among MSM is associated with acute HIV infection. If pooled HIV RNA testing is not performed on those with negative HIV rapid tests, over 10-15% of testers in high-risk groups may be missed and sent home unaware of their actual infection status at the height of their infectivity and sexually risky behaviors.…”
Section: Discussionsupporting
confidence: 65%
“…Those viral load data are important for scientists modelling the contribution of acute HIV infection in HIV transmission dynamics and reinforce the importance and urgency of expanding screening for acute HIV infection to accelerate HIV control among high-risk populations in the United States. 4-9,13,23-27 A recent study found that testing for acute HIV infection was cost-effective in preventing new HIV infections among at risk MSM in San Diego as well as other MSM populations with similar HIV prevalence but lower proportions of diagnosis of acute HIV infection. 28 …”
Section: Discussionmentioning
confidence: 99%
“…Solutions to these issues may be addressed by leveraging existing resources to provide PrEP services, including cross-training of staff (e.g., health educators, pharmacists, nurses) to deliver PrEP counseling [52]. Similar to the movement away from “HIV exceptionalism” and integration of routine HIV testing into primary care settings [53],[54], PrEP delivery will require integration into primary care settings to maximize PrEP coverage of at-risk individuals. Experience and lessons learned from PrEP implementation programs in more specialized settings (e.g., STD/HIV clinics) can be used to develop user-friendly tools (e.g., patient education and counseling materials, checklists for PrEP prescribing) to facilitate primary care providers delivering PrEP in their practices [50].…”
Section: Next Steps For Prepmentioning
confidence: 99%
“…It is estimated that 25%-50% of patients who are tested for HIV through the traditional method (laboratory venipuncture and a wait period of several days to weeks) never return for their test results (CDC, 2006a;Hoots & Wohl, 2008;Losina et al, 2010). The development of rapid HIV-1/2 antibody tests allows for highly accurate test results within 20 minutes (Smith, Zetola, & Klausner, 2007).…”
Section: The Centers For Disease Control and Preventionmentioning
confidence: 99%